AKIBAT HUKUM TERHADAP PENERBITAN SERTIPIKAT HAK MILIK ATAS TANAH YANG SYARAT ADMINISTRASINYA TIDAK DI TANDA TANGANI OLEH SAKSI BATAS - Tutus Chariesma Putra (Universitas 17 Agustus 1945 Samarinda, 2013)
ABSTRACTProvide legal certainty and protection to the holders of rights in a parcel of land or apartment units that can easily be proven himself as the holder of the rights, the National Land Agency (BPN) as an authorized institution in terms of the legality of the soil, to provide legal certainty by issuing certificates to the ground plane or apartment units , perform first the measurement on the object plane land or apartment units in question, which should be set in advance the boundaries of the land to be measured with the consent of the parties that the land bordering the field . However , the role of witnesses in determining the limits of the boundaries of land parcels for a certificate peneribitan kandangkala neglected plots of land that would later become debates and legal issues that could harm either party , even it is not impossible that the institution has the legal authority to blame land or subject to legal sanctions for negligence in providing the certificate issuance policy.